Kampung Malays: surviving modernity - Moten, Abdul Rashid; Wahiddin, Mohamed Ridza (IIUM Press, International Islamic University Malaysia, 2019)
Modernization has led to changes in people’s lifestyle and their worldviews. The traditional form of life was governed by a set of community-validated patterns of behaviour with individuals assuming a relatively fixed role in society. Modernity led to the replacement of communal solidarity with interest associations. It encourages migration from rural areas to urban centres and makes people insecure due to the loss of family ties. Malaysia is also affected by its march towards industrialization and modernization which gave rise to a sizable new middle class. The traditional ways of life of the Malays have been affected. Nevertheless, the distinctive cultural traits endure over long periods of time albeit with the active reinvention and reincorporation of certain traits of modernization. To what extent has modernization changed the Malaysian landscape and how much their inhabitants especially the Kampung Malays have embraced this line of progress. How has this development impacted the rural grassroots level individuals? The traditions that survived after these tumultuous changes are the focus of this book which is based upon a socio-economicand religious survey carried out on selected samples and thus renders it original in the empirical sense.